1997
DOI: 10.1016/s0275-5408(96)00084-1
|View full text |Cite
|
Sign up to set email alerts
|

Eye drop container delivery: a source of response variation?

Abstract: Variations in response to topically applied ocular drugs (e.g. mydriatics and cycloplegics) and their possible aetiology have been studied previously. It appears that individual patient differences, external influencing factors and the characteristics of the particular drug may all govern the response. One factor worthy of note in this regard is the possibility of variation in the drug volume instilled. Single-use eye drop containers known as Minims are commonly used during ophthalmic diagnostic procedures. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However none of these three factors correlated significantly (Pearson correlation analysis, P > 0·05) with precision or mean volume delivered from the Arovit dropper for the single‐drop or five‐drop tests (Table 2). Previous findings (9) suggested that density has a weak, but significant, positive correlation with drop mass and that surface tension has a significant positive correlation with drop mass. Similarly, Van Santvleit and Ludwig (10) showed surface tension to have significant regression with drop mass.…”
Section: Influence Of Physical Properties Of Liquids On Volumes Delivmentioning
confidence: 85%
See 2 more Smart Citations
“…However none of these three factors correlated significantly (Pearson correlation analysis, P > 0·05) with precision or mean volume delivered from the Arovit dropper for the single‐drop or five‐drop tests (Table 2). Previous findings (9) suggested that density has a weak, but significant, positive correlation with drop mass and that surface tension has a significant positive correlation with drop mass. Similarly, Van Santvleit and Ludwig (10) showed surface tension to have significant regression with drop mass.…”
Section: Influence Of Physical Properties Of Liquids On Volumes Delivmentioning
confidence: 85%
“…German et al. (9, 11), and Van Santvliet and Ludwig (8) showed that the further eye dropper bottles are held away from the vertical the smaller the drop volume delivered. According to Tate's law (Eq.…”
Section: Influence Of Residual Volume and Angle Of Delivery On Volumementioning
confidence: 99%
See 1 more Smart Citation
“…This is pertinent because characteristics of the liquid greatly affect drop size (1). Second, the handling angle of the container was vertical; consistency in handling angle is necessary since holding vertically produces a larger drop than holding at an angle (1, 2). Third, the pressure on the dispenser was released and the bottle turned upright between each drop to allow forces to equilibrate.…”
Section: Discussionmentioning
confidence: 99%
“…The drop sizes of many commercially available topical ocular medications are reported to be from 25 up to 70 µL (Shell 1982;Lederer and Harold 1986;Urtti and Salminen 1993). The variation of drop size is caused by three main factors: the dropper tip design, the physicochemical properties of the solution, and the patient's manner of handling the dropper bottle, such as the dispensing angle and rate (van Santvliet 1999;Sklubalova and Zatloukal 2005;German et al 1997). …”
Section: Introductionmentioning
confidence: 99%